Development of a PCB-based passive capacitive sensor for fluidic flow detection - Nhu Cuong Nguyen; Bao Anh Hoang; Trung Kien Do; Thanh Tung Bui; Duc Trinh Chu; Quang Loc Do (Vietnam Journal of Science, Technology and Engineering, 2023)
A passive wireless sensor system integrated with capacitive fluidic flow detection is proposed and developed based on the printed circuit board (PCB) technique. The capacitive sensing structure consists of PCB-based electrodes enclosing an insulating pipe that contains the fluidic flow of interest. The conductivity of the fluidic flow and the appearance of foreign objects within the flow can be determined by analysing the resonant frequency of the detection path in the proposed system. Experimental results demonstrate that the resonant frequency increases according to the increase in electrical conductivity of the fluidic flow. In addition, the sensing performance is also confirmed by the detection of sizes and electrical conductivities of NaCl droplets passing through the detection zone. Furthermore, this work indirectly verifies the effectiveness and feasibility of the integration of passive wireless sensing technique into the fluidic flow detector by using the PCB fabrication technique and demonstrates great potential for use in various applications in biomedical and chemical fields, especially in biomedical applications.